The Influence of Social Media as a Health Promotion Tool for Dengue Fever Prevention - Wa Ode Kasmalia; La Ode Hamiru; Lodes Hadju (Miracle Journal of Public Health, 2025)
Dengue fever tends to increase and spread more widely. Based on data recorded by the Kendari City Health Office, a total of 1,689 people were affected by dengue fever, and 12 people died. The purpose of this study was to determine the effect of using social media as a means of health promotion in the prevention of dengue fever among students at Kendari 2 Public Vocational School. The design used was a one-group pretest-posttest design. The population in this study consisted of 439 students, with a sample size of 81 students selected using simple random sampling. The data were analyzed using univariate and bivariate analysis using the McNemar test. The data were presented in tables and narratives. The results of the analysis showed that social media as a means of health promotion had an effect on increasing students' knowledge and attitudes towards dengue fever prevention (p-value = 0.000). In conclusion, social media has an effect as a means of health promotion to increase students' knowledge, attitudes, and actions towards dengue fever prevention. It is hoped that social media can be used as a means of health promotion to increase students' knowledge, attitudes, and actions towards dengue fever prevention.